2009
DOI: 10.1016/j.yexcr.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of mesenchymal stem cells into dystrophin-deficient mice is not accompanied by functional recovery

Abstract: Mesenchymal stem cell preparations have been proposed for muscle regeneration in musculoskeletal disorders. Although MSCs have great in vitro expansion potential and possess the ability to differentiate into several mesenchymal lineages, myogenesis has proven to be much more difficult to induce. We have recently demonstrated that Pax3, the master regulator of the embryonic myogenic program, enables the in vitro differentiation of a murine mesenchymal stem cell line (MSCB9-Pax3) into myogenic progenitors. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 63 publications
0
59
0
4
Order By: Relevance
“…MSCs have been shown to be capable of skeletal myogenesis (65). However, recently, Perlingeiro and colleagues demonstrated that although Pax3 activation enabled the in vitro differentiation of murine and human MSCs into MyoD + myogenic cells, these cells failed to cause functional muscle recovery in mdx mice, despite good engraftment (66). The reason for this failure remains unclear.…”
Section: Other Myogenic Progenitorsmentioning
confidence: 99%
“…MSCs have been shown to be capable of skeletal myogenesis (65). However, recently, Perlingeiro and colleagues demonstrated that although Pax3 activation enabled the in vitro differentiation of murine and human MSCs into MyoD + myogenic cells, these cells failed to cause functional muscle recovery in mdx mice, despite good engraftment (66). The reason for this failure remains unclear.…”
Section: Other Myogenic Progenitorsmentioning
confidence: 99%
“…More immature subpopulations of myogenic progenitors sorted by pre-defined cell surface markers from skeletal muscle are able to contribute to the satellite cell pool and give improved engraftments in dystrophin-deficient mdx mice [16][17][18]. Different populations of myogenic cells have also been derived from vascular progenitor cells [9], adipose-derived progenitors [10], genetically modified mesenchymal stem cells [19], and embryonic stem cells [20]. While the efficiency of engraftments is improving, muscle function has been limited, and variable [21,22], and tumorigenesis has been reported in studies [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Dystrophin was detected in 6%-11% of muscle fibers in the mdx mouse, a murine model for DMD [45][46][47] after transplantation of murine BM-MSCs transduced with a human microdystrophin gene [45,47] or human BM-MSCs [46]. However, only one of these studies demonstrated conclusively that the dystrophinpositive myofibers detected originated from the donor cells by examining the percentage of dystrophin-positive fibers that expressed human microdystrophin [46]. This distinction is relevant, because the low number of dystrophin-positive myofibers detected might have been naturally arising "revertant" fibers, which are detected at low levels in dystrophic muscle, rather than fibers generated by donor MSCs.…”
Section: Mesenchymal Stem Cells For Repair Of Dystrophic Skeletal Musclementioning
confidence: 99%
“…This finding is similar to that from a previous report in which human and rat green fluorescent protein (GFP)-positive BM-MSCs generated GFP-positive Pax7+ satellite cells in murine skeletal muscle that subsequently generated GFP-positive myofibers after cardiotoxin damage [49]. BMMSCs, therefore, could have the potential to generate new, dystrophin-expressing myofibers and contribute to the satellite cell niche in dystrophic muscle; however, they would do so at low rates, which is likely the reason for the lack of functional improvement [46,47].…”
Section: Mesenchymal Stem Cells For Repair Of Dystrophic Skeletal Musclementioning
confidence: 99%